First climatology of F-region UHF echoes observed by the AMISR-14 system at the Jicamarca radio observatory and comparison with the climatology of VHF echoes observed by the collocated JULIA radar - (:unkn) unknown (Elsevier BV, 2024)
Coherent backscatter radar observations made at the Jicamarca Radio Observatory (JRO) have contributed significantly to our understanding of equatorial F-region irregularities. Radar observations, however, have been made predominantly at the Very-High Fr...
Keywords: Radar ionosférico; Jicamarca